Germline variation in colorectal risk Loci does not influence treatment effect or survival in metastatic colorectal cancer. - Hanna K Sanoff; Lindsay A Renfro; Pradeep Poonnen; Pratibha Ambadwar; Daniel J Sargent; Richard M Goldberg; Howard McLeod (PLoS ONE)
Background Colorectal cancer (CRC) risk is partly conferred by common, low-penetrance single nucleotide polymorphisms (SNPs). We hypothesized that these SNPs are associated with outcomes in metastatic CRC. Methods Six candidate SNPs from 8q24, 10p14, 15q13, 18q21 were investigated for their association with response rate (RR), time to progression (TTP) and overall survival (OS) among 524 patients treated on a phase III clinical trial of first-line chemotherapy for metastatic CRC. Results rs10795668 was weakly associated with TTP (p = 0.02), but not RR or OS. No other SNPs carried statistically significant HRs for any of the primary outcomes (RR, TTP or OS). Conclusion Common low-penetrance CRC risk SNPs were not associated with outcomes among patients with metastatic CRC.